Palliative Care Management - Naiane Santos, Leifa; Silva Rigo, Rosângela; Sezara Almeida, Julia; Medeiros Limberger, Luana (Seven Editora, 2023)
Management in palliative care contemplates several important aspects, from its identification, implantation, and reception of the patient with the family, seeking to clarify doubts, expanding attention in care, within the principles of action in palliative care with reinforcement of life, its quality, until the passing of death. The study aims to assist in the applicability of palliative care plans at different levels of medical care, providing a reduction in harm and hospitalizations/interventions, alleviating pain, and suffering to the patient and his support network. Palliative care plans represent great relevance in health care, presented through a narrative bibliographic review, based on scientific data, from UpToDate, PubMed, Scielo, BVS, and Google Scholar, identifying and highlighting some challenges that discourage the collaboration of quality assistance, due to an inefficient public policy, desensitization of health managers, a predominantly paternalistic/curative medicine, the absence in the public health network of multidisciplinary professionals trained to work in palliative care, verifying the need to develop a permanent and social education, implementing patient-centered medicine and its psychosocial aspects.DOI: https://doi.org/10.56238/devopinterscie-143